The changing market for distribution: implications for Exel Logistics - Bence, Valerie (Cranfield University, 1995)
This paper has been written to compliment a previous Working Paper (The Evolution of a Distribution Brand: The Case of Exel Logistics) and to some extent allows that company’s development (1989- 1993) to be placed in the context of marketplace and industry changes. I wish to examine three of the main trends affecting the distribution industry over the same period. Firstly, the move towards the centralisation of operations by both manufacturers and retailers, secondly at the debate surrounding contracting-out and in-house distribution activities and finally, the issues under consideration must be seen in a wider context - that of distribution and the Single European Market (SEM), which could be said to be the most important development facing the distribution industry for many years. These trends will be discussed in some detail and, where appropriate, from Exel Logistics’ perspective in order to consider how far the company has gone both in dealing with marketplace changes and in achieving its aims.